PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS III DENGAN MEDIA POWER POINT INTERAKTIF MACAN (MATERI PECAHAN) - Ammylia Prihatini Sulhaliza; Agti Fiana Qoirul Ananta; Diana Ermawati (STAI Nurul Falah Airmolek, 2024)
This research aims to improve the low level of mathematical problem solving regarding fractions using Interactive Power Point media for class III students at SD 2 Panjunan. Data collection techniques in this research used observation, interviews and documentation techniques, tests. The instruments of this research are interview sheets, observation sheets, and test question sheets. The method in this research uses the classroom action research method. The subjects in this research were class III students at SD 2 Panjunan with a total of 26 students. This research uses the Kemmis and Mc Taggart model research design, where each cycle or round consists of several stages which include, planning, action, observation, and reflection. The research results in Cycle I showed an average of 42% where the level of learning success was still low, and in cycle II after using interactive power point media it showed an average of 88% with a very good category, this shows that the application of interactive Power point in the learning process with fraction material can improve mathematics learning outcomes for class III students at SD 2 Panjunan. The conclusion of this research is that Interactive Power Point media can improve students’ mathematical problem solving abilities in fraction material.